Constituição do sujeito organizacional: leituras de Foucault sob o enfoque dos estudos organizacionais - Aquino, Magno Geraldo de (2015)
With this study in form of Theoretical Trial, we aimed at reflecting upon issues concerning the organizational subject based on readings authors/researchers conduct of Michel Foucault. This will allow us the argumentation regarding the processes from which individuals are constituted as subjects by means of practices and power relations that occur within the organizations throughout history. We focus on the relation between the subjection processes and the subjectivation practices, and the games of truth within the organizational context. In the perspective of the foucaudian studies, the workings of power presuppose that the individuals are free, acting within a space of possibilities in which they seek to subjectify themselves, being covered by mechanisms that make feasible and, at the same time, restrict liberty. Fundamentally, the power relations also constitute strategic imposition and resistance relations, reinforced or opposed by the subject, in a power shift that seeks to maintain or create new mechanisms that guarantee the continuity of the exercise of power. This work was developed in the form of three main chapters. In the first, we analyze the issues concerning a significant change operated by Foucault in his analyses on power relations. Without contradicting or refusing the analyses on disciplinary power, Foucault reinserts them in a more ample discussion, in which life, in its biological reality and considered the “natural” functions and demands of the species, such as birth, disease and death, is invested of biopower and biopolitical mechanisms. In the second chapter, we sought to survey the fundamental elements of power analytics, considered under the perspective of the relation between knowledge and power, in addition to the notion of power positivity, in which we consider that the power creates not only disciplinary states, but also knowledge, practices and subjectivities, by means of a dialog between biopolitics and governmentality. In the third chapter, we analyzed the issues concerning the relation between subject, power and truth, and the constitution processes of the organizational subject, based on practices of the self, in which we seek to reflect on how an individual, in his specific historic practice, becomes a subject. Finally, we sought to build arguments to evidence the workings of power relations between the subjects and the institution in which they act, emphasizing on how the practices the individual performs within the organizational context influence his constitution as subject. As final considerations, we synthetize the reflections undertaken in the course of this work, as well as present new study possibilities for the theme of subject constitution, inspired by foucaudian ideas.